Boredom, Cohesion, and Transformation in Nick Drnaso’s Beverly - David Callahan (European Journal of American Studies)
Nick Drnaso’s Beverly (2016) is a loosely-connected assemblage of graphic stories focused on suburban Midwest America. The stories appear to represent suburban life as so monotonous that experiencing intensity or meaningful interactions is almost impossible. One potential avenue to break the monotony is that of actively transforming the self, but transformative options are revealed to be superficial and ultimately unable to counter the experience of life as lack and isolation. In turn, the possibility that the repetitive interactions of everyday life in fact provide known and secure structures, compensating for their flat sameness, is revealed to be hollow by most characters’ frustrations, melancholy, and lack of joyful connection with others. While the marginalized characters of Sal and Tyler may suggest the possibility of rejecting the boredom of everydayness, it comes at the cost of meaningful connection with others. By representing this everydayness through bland graphic strategies, Drnaso might seem to run the risk of having created a book that is itself boring, and yet his precise observation and subtle use of limited panel arrangements and color palette overcome the risk and make Beverly an acute exploration of contemporary suburban American life as boredom.